Increasing the drying unit energy efficiency through with thermoelectric modules - D. A. Tikhomirov; A. V. Khimenko; A. V. Kuzmichev (Сельскохозяйственные машины и технологии)
Drying food products and materials is one of the most common methods in processing raw materials, yet it remains an energy-intensive process. The main drawback of traditional electric convective household dryers is the loss of heat and the wet waste drying agent into the environment. Furthermore, such units are characterized by uneven heating of the dried product, attributed to a temperature decrease and increasing humidity from bottom to top. (Research purpose) The purpose of this study is to conduct laboratory experiments on the drying process of apples focusing on evaluating the energy consumption required to evaporate 1 kilogram of moisture using a newly developed convective thermoelectric drying unit and compare its energy efficiency with mass-produced convective dryers. (Materials and methods) The findings from theoretical and experimental studies facilitated the development of a functional diagram and a laboratory prototype of a convective thermoelectric dryer using a thermoelectric heat pump. The drying process involves the utilization of a drying agent (heated air) with partial air recirculation, and heat recovery from the exhaust air. (Results and discussion) Temperature variations at designated control points and the relative humidity of the drying agent at both inlet and outlet of the developed unit were graphed and analyzed. The parameters of apples before and after drying in the thermoelectric drying unit are compared with those dried in a conventional household convective dryer. The study has resulted in developing an electrical control circuit for a thermoelectric drying unit and providing expressions to calculate the hot junction radiator of an air-to-air thermoelectric heat pump integrated into the developed drying unit. (Conclusions) The study estimated the average heat recovery by the cold junction radiator of a thermoelectric heat pump from the exhaust drying agent during the drying process, amounting to approximately 20 percent of the total energy consumption by the thermoelectric drying unit from the electrical grid. The research findings demonstrate that the laboratory prototype offers a more consistent drying process for the product. This is attributed to the incorporation of side air channels and a more efficient arrangement of the drying agent’s movement within the working chamber, as opposed to traditional convective dryers. These conclusions are substantiated by the test results. It is illustrated that the use of a developed thermoelectric heat pump with heat recovery from the waste drying agent can lead to a reduction in the installed power capacity of the drying agent heater and a decrease in the energy consumption for the drying process in the developed convective thermoelectric drying unit compared to mass-produced household convective dryers.